Haurabelle / Nur Nasuha Ibrahim - Ibrahim, Nur Nasuha (2021)
“BIAR MURAH, ASALKAN CANTIK!!” is a trademark for Haurabelle clothing business. The main objective is that the business want to achieve is to offer variety clothes, in term of designs, colours, materials to the customers in affordable price. According to the customers feedback, most of them like the clothes because of their item is loose and baggy style. This clothes also wudhu’ friendly and can replace telekung to prayed. This product also liked by many due to the cheap and affordable price. Due to the pandemic Covid-19, this product still operating same as shipping delivery. Haurabelle is a good product to buy because of their comfy and loose item. Also their affordable price. Hopefully this business can further be expanded to many people as the business keep on growing.